Molecular changes in the intestinal barrier function of broiler chickens with bacterial chondro-necrosis and osteomyelitis - Maksymchuk, Ya.; Максимчук, Я.; Masjuk, D.; Masiuk, Dmytro; Masiuk, D. N.; Masiuk, D. M.; Masiuk, D.; Masyuk, D. N.; Masyuk, D. M.; Masyuk, D.; Masjuk, Dmytro; Masiuk, Dmytro M.; et al. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv, 2026)
The aim of the study was to evaluate the characteristics of gene expression of inflammation, apoptosis, and intestinal barrier function markers in broiler chickens with bacterial chondronecrosis and osteomyelitis, as well as under the influence of a composition of organic (fatty) acids. The study was conducted on ROSS-308 broiler chickens under commercial production conditions. Experimental groups were formed retrospectively according to clinical status. Samples of the small and large intestine, chyme, and feces were collected for molecular analysis. The relative expression levels of the genes TNF-α, IL-1β, Caspase-9, Claudin-1, Occludin, MUC-2, and Fibronectin were determined using the RT-qPCR method. It was established that under pathological conditions, a redistribution of the inflammatory response occurs between the tissue and luminal compartments of the intestine, manifested by decreased TNF-α expression in the small intestine and increased IL-1β expression in chyme and feces. Changes in Caspase-9 expression indicate modification of apoptotic processes, with a tendency toward suppression in tissues and possible enhancement in the luminal environment. Impairment of the intestinal barrier function was revealed, as confirmed by decreased expression of Claudin-1 and MUC-2 in tissues and feces, as well as multidirectional changes in Occludin expression. Increased Fibronectin expression in the luminal compartment indicates activation of extracellular matrix remodeling processes and destructive-reparative changes in the mucous membrane. The obtained results indicate a profound restructuring of the functional state of the intestine in bacterial chondronecrosis and osteomyelitis, accompanied by an imbalance between inflammation, apoptosis, and barrier function. The use of a composition of organic acids may modify the nature of the intestinal response, contributing to the limitation of inflammation in tissues and the maintenance of intestinal barrier integrity. Метою дослідження було оцінити характеристики експресії генів запалення, апоптозу та маркерів функції кишкового бар'єру у бройлерних курчат з бактеріальним хондронекрозом та остеомієлітом, а також під впливом композиції органічних (жирних) кислот. Дослідження проводилося на бройлерних курчатах ROSS-308 в умовах промислового виробництва. Експериментальні групи були сформовані ретроспективно відповідно до клінічного стану. Для молекулярного аналізу були зібрані зразки тонкої та товстої кишки, хімусу та фекалій. Відносні рівні експресії генів TNF-α, IL-1β, Caspase-9, Claudin-1, Occludin, MUC-2 та Fibronectin визначалися за допомогою методу RT-qPCR. Було встановлено, що за патологічних умов відбувається перерозподіл запальної реакції між тканинним та просвітним відділами кишечника, що проявляється зниженням експресії TNF-α у тонкому кишечнику та підвищенням експресії IL-1β у хімусі та фекаліях. Зміни експресії Caspase-9 свідчать про модифікацію апоптотичних процесів з тенденцією до пригнічення в тканинах та можливим посиленням у просвітному середовищі. Виявлено порушення функції кишкового бар'єра, що підтверджується зниженням експресії Клаудину-1 та MUC-2 у тканинах та калі, а також різноспрямованими змінами експресії Оклюдину. Підвищена експресія фібронектину в просвітному компартменті свідчить про активацію процесів ремоделювання позаклітинного матриксу та деструктивно-репаративні зміни слизової оболонки. Отримані результати свідчать про глибоку перебудову функціонального стану кишечника при бактеріальному хондронекрозі та остеомієліті, що супроводжується дисбалансом між запаленням, апоптозом та бар'єрною функцією. Використання композиції органічних кислот може змінювати характер кишкової реакції, сприяючи обмеженню запалення в тканинах та підтримці цілісності кишкового бар'єру.
Молекулярні зміни у функції кишкового бар'єру бройлерних курчат з бактеріальним хондронекрозом та остеомієлітом
Масюк Дмитро Миколайович https://orcid.org/0000-0002-2800-2580
Keywords: broiler chickens; бройлерні курчата; intestine; кишечник; barrier function; бар'єрна функція; Caspase-9; каспаза-9; Claudin-1; клаудин-1; Occludin; окклюдин; Fibron-ectin; фіброн-ектин; bacterial chondronecrosis; бактеріальний хондронекроз; organic acids; органічні кислоти; gene expression; експресія генів; RT-qPCR; зворотна ПЛР з кількісною транскрипцією (RT-qPCR)